Penerapan Model Pembelajaran Berbasis Masalah (Problem Based Learning) untuk Meningkatkan Hasil Belajar Geografi Pada Materi Dinamika Perubahan Hidrosfer Siswa Kelas X SMA Negeri 1 Mangoli Utara - Darling Surya Alnursa (Jurnal Ilmiah Wahana Pendidikan, 2022)
Learning geography is learning that discusses more about social problems that are logical in nature and identical to rote memorization, so that if teachers are not creative in applying learning models, students will feel bored in participating in classroom learning and this will certainly affect student learning outcomes. The low activity and results of students in participating in teaching and learning process activities are caused by, students lack the courage to express opinions during teaching and learning, students lack the ability to formulate their own ideas, besides that there is less active interaction between students and teachers and students do more note-taking and listening activities. This situation, after the researchers looked at it, it turned out that the learning methods used were less varied and innovative. The type of research used in this research is Classroom Action Research (CAR), using a qualitative research approach. With the aim of improving geography learning outcomes in class X SMA Negeri 1 Mangoli Utara after learning is carried out using a problem based learning model. Based on the results of the research in the first cycle, it shows that the ability of students' knowledge about the dynamics of hydrospheric changes. The average value obtained by students on this test is 61.74, the test results show that most students have not been able to solve problems on the dynamics of hydrospheric change and the percentage of students who achieve completeness is 47.83%. While in the second cycle the students' knowledge ability which shows that the average value obtained on this test has increased, namely 74.61, on the test almost all students have been able to solve problems with the material and the percentage of students who achieve completeness is 82.60 %.